PENTINGNYA AKUNTANSI SYARIAH DI ERA MODERN - Yuni, Ika Darma; Insani, Fadhillah; Nurlaila, Nurlaila (Jurnal Ilmu Akuntansi dan Bisnis Syariah (AKSY), 2023)
This essay aims to determine the value of Islamic accounting in the contemporary world. The most famous examples of accounting fraud techniques are the Enron and Arthur Anderson scandals. Naturally, it is unlikely that this state of affairs will occur again in the future. The key elements of the Islamic accounting concept are explained in this essay. The descriptive qualitative research methodology used in this essay. And it can be concluded that despite the fact that many businesses are starting to transition to using Islamic principles, Islamic accounting still feels isolated in Muslim-dominated countries. Many people still believe that this is all a ruse because they have not fully implemented the concept of sharia. Sharia accountants understand the principles of the Islamic religion and will realize that if they engage in deviant behavior, they will not only be punished by their superiors but will also be held accountable for their behavior before Allah swt. As if it is still being debated, sharia accounting is important because everything is accounted for not only to superiors or management.